1999
DOI: 10.1038/sj.bjc.6690622
|View full text |Cite
|
Sign up to set email alerts
|

Laminin mediates tethering and spreading of colon cancer cells in physiological shear flow

Abstract: Summary Under the physiological shear condition, cultured colon cancer cells bound to laminin (LM), but not to fibronectin or vitronectin. Most of the tethered cells did not roll, but arrested immediately and spread within 10-30 min on LM under the continuous presence of shear flow. The tethering of Colo201 was partially inhibited by monoclonal antibodies (mAbs) to α6 integrin and a combination of mAbs to β1 and β4 integrins, but not by mAb to 67KD laminin receptor. Some Colo201 cells still tethered at 4°C. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
(47 reference statements)
3
33
0
Order By: Relevance
“…Furthermore, biochemical interactions between adhesion molecules and their ligands during tumor cell adhesion within circulatory systems appear to be influenced by biophysical factors, such as shear stress caused by fluid flow, and cellular and soluble components of the circulating fluid. [15][16][17] Intravital microscopy technologies have been recently used to investigate metastatic tumor cell adhesion within host organ microcirculation, such as in liver and lung. 10 -14 In these studies contradictory results were reported regarding the type of entrapment (mechanical entrapment 10 -12 versus active cell adhesion 14,18 ) and the requirement of invasion into host organ parenchyma (invasion 10,11,13,18 versus intravascular proliferation 14 ).…”
mentioning
confidence: 99%
“…Furthermore, biochemical interactions between adhesion molecules and their ligands during tumor cell adhesion within circulatory systems appear to be influenced by biophysical factors, such as shear stress caused by fluid flow, and cellular and soluble components of the circulating fluid. [15][16][17] Intravital microscopy technologies have been recently used to investigate metastatic tumor cell adhesion within host organ microcirculation, such as in liver and lung. 10 -14 In these studies contradictory results were reported regarding the type of entrapment (mechanical entrapment 10 -12 versus active cell adhesion 14,18 ) and the requirement of invasion into host organ parenchyma (invasion 10,11,13,18 versus intravascular proliferation 14 ).…”
mentioning
confidence: 99%
“…Strongly adherent cells may increase their migration capacity through a decrease of their adhesion to extracellular matrix. While subtle, we observed a differential adhesion capacity of KD cells, namely for laminin, a non-collagenous extracellular matrix critical in colon cancer and linked to tumor angiogenesis, epithelial-mesenchymal transition and metastasis (Guess et al, 2009;Kitayama et al, 1999;Simon-Assmann et al, 2011). Accordingly, this observation may partially explain the differential migration phenotype between low and high UGT1A_i2 expressing cell lines.…”
Section: Discussionmentioning
confidence: 52%
“…In our previous report (31) CD49f, also known as integrin α6 (ITGA6), is a major laminin receptor and mediates cell adhesion (16,18,19,21). In colon cancer, expression of CD49f has been reported to be associated with tumor cell invasion and metastasis via integrin-mediated cell signaling and adhesion to the extracellular matrix (16,18,19,21). CSCs in various cancers show high metastatic potency (12)(13)(14)(15).…”
Section: Ht29 Caco2 -------------------------------------------------mentioning
confidence: 99%
“…We also assessed CD49f and CXCR4 expression, because CD49f was reported as a marker of breast (34), prostate (35) and glioblastoma (36) CSCs and CXCR4 was reported to be a marker of pancreas CSCs (12). CD49f and CXCR4 is also known to deeply associate with cancer metastasis (12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The expression of CD44 was drastically reduced by NaBT treatment (rate of change, -99.2% in HT29 and -97.2% in Caco2; average, -98.2%).…”
Section: Screening Of Colorectal Cancer Stem Cell Markers By Differenmentioning
confidence: 99%
See 1 more Smart Citation